2011
DOI: 10.1073/pnas.1116821108
|View full text |Cite
|
Sign up to set email alerts
|

Functional reconstitution of human eukaryotic translation initiation factor 3 (eIF3)

Abstract: Protein fate in higher eukaryotes is controlled by three complexes that share conserved architectural elements: the proteasome, COP9 signalosome, and eukaryotic translation initiation factor 3 (eIF3). Here we reconstitute the 13-subunit human eIF3 in Escherichia coli , revealing its structural core to be the eight subunits with conserved orthologues in the proteasome lid complex and COP9 signalosome. This structural core in eIF3 binds to the small (40S) ribosomal subunit, to translation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
166
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(180 citation statements)
references
References 57 publications
12
166
2
Order By: Relevance
“…This proposed model of 40S binding mode of eIF3 is in accordance with that available for yeast (Valasek et al 2003). A recent study on the reconstitution of human eIF3 has revealed that an octameric subcomplex of eIF3 comprising subunits e, f, h, k, l, and m and truncated fragments of subunits a and c exhibits a striking structural resemblance to the previously determined cryo-EM structure of native human eIF3 (Sun et al 2011).…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…This proposed model of 40S binding mode of eIF3 is in accordance with that available for yeast (Valasek et al 2003). A recent study on the reconstitution of human eIF3 has revealed that an octameric subcomplex of eIF3 comprising subunits e, f, h, k, l, and m and truncated fragments of subunits a and c exhibits a striking structural resemblance to the previously determined cryo-EM structure of native human eIF3 (Sun et al 2011).…”
Section: Introductionsupporting
confidence: 56%
“…Such a reconstitution system would, on the one hand, provide new strategies for a detailed kinetic and thermodynamic dissection of translation initiation in eukaryotes and, on the other hand, facilitate structural studies of eIF3 and its interaction partners. Recently, Sun et al (2011) described the reconstitution of human eIF3 using recombinantly expressed and purified subcomplexes. Using this system, the importance of an octameric subcomplex of eIF3 for binding to the 40S ribosomal subunit and to the hepatitis C viral (HCV) internal ribosome entry site (IRES) was demonstrated (Sun et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[119]. Intriguingly, eIF3 is still capable of binding the IRES after being subjected to limited proteolysis [120], and a reconstituted octamer of eIF3 (a, c, e, f, h, k, l, m) is capable of high-affinity binding to an RNA fragment containing domain IIIa-c [121]. Although a full eIF3 complex appears to be important for efficiently forming 48S complexes [121], this suggests that IRES : eIF3 affinity does not require the full complex.…”
Section: (D) the Structural And Functional Basis Of Hcv Ires : Eif3 Imentioning
confidence: 99%
“…The PCI subunits form a horseshoe-shaped structure and the MPN domains form a heterodimer, which are connected by a large helical bundle, to which all subunits contribute (13,17,18). Each of these eight subunits has paralogs in the COP9/signalosome (CSN) and the elongation initiation factor 3 (eIF3), which likely adopt a similar architecture (18)(19)(20)(21).The lid strengthens the interaction between the CP and RP (17) and deubiquitylates substrates before their processing by the AAA-ATPase module and the CP. Cleavage of polyubiquitin…”
mentioning
confidence: 99%